Geochemical Assessment Of Soils Affected By The Jawahar Nagar Dumpyard (International Journal of Environmental Sciences, 2025)
The proliferation of unregulated municipal solid waste (MSW) landfills in the Global South poses escalating threats to soil and environmental health. This study presents a comprehensive geochemical investigation of soils surrounding the Jawahar Nagar dumpsite in Telangana, India, one of South India’s largest and most environmentally burdened landfill zones. Soil samples were collected from three spatially distinct locations (adjacent to the landfill, leachate-affected basin, and downstream runoff path) during both pre- and post-monsoon periods of 2021 and 2022. A suite of physicochemical parameters, including pH, organic content, ionic species, and salinity indicators alongside trace heavy metal concentrations, was analyzed using standard protocols and ICP-OES. Results revealed seasonal amplification of contamination, with soils near the landfill exhibiting severe ionic enrichment (sulphates up to 6100 mg/kg; potassium up to 1550 mg/kg) and elevated heavy metal concentrations, particularly post-monsoon, when lead, chromium, and zinc peaked at 15.0 mg/kg, 9.1 mg/kg, and 13.6 mg/kg, respectively. Cobalt, tin, cadmium, arsenic, and methyl mercury were also consistently detected, signifying chronic leachate infiltration and pollutant transport. Correlation analysis highlighted strong dependencies among pH, salinity, and organic matter, underscoring the landfill’s role in restructuring soil geochemistry. The findings offer a spatially resolved, seasonally sensitive framework for identifying contamination hotspots, guiding remediation priorities, and informing policy decisions on buffer zoning and ecological restoration. This study serves as a critical diagnostic reference for future research and sustainable management of landfill-impacted landscapes across developing urban regions.